The Management of Type 1 Diabetes in Primary School: Review of the Literature. (March 2013) - Marks, Anne; Wilson, Valerie; Crisp, Jackie
<x xml:space="preserve">Abstract</x> Type 1 diabetes is one of the most common chronic health conditions in childhood. The introduction of intensive insulin therapy and the rising prevalence of diabetes in younger children has increased the need for involvement of diabetes educators and school personnel in school diabetes care. School encompasses a significant proportion of a child's day, therefore diabetes treatment at school needs to be optimal or the child will have poor metabolic control. The aim of this literature review is to examine diabetes management in the early primary school setting. The main areas of diabetes management explored are: type, provision, and location of treatment, the impact on the child, and the role of the credentialed diabetes educator. The review identifies that the majority of children are not receiving intensive diabetes treatment at school. Younger children require more assistance with care and may be disadvantaged due to lack of appropriate school staff support. Most schools do not have nurses to assist with diabetes care, therefore teaching and administration staff are utilized. The use of insulin pump therapy may increase access to insulin at school, as children and teaching staff appear more confident with this method of delivery than injections. Treatment is frequently performed away from the classroom and can impact on class attendance, metabolic control, and emergencies. Diabetes educators need to work in collaboration with children, parents, and school personnel to ensure diabetes care is fully integrated into the school day.